Transcriptomic and metabolomic analyses for the mechanism underlying anthocyanin synthesis during the growth and development of purple eggplant (Solanum melongena L) - Yang, Ting; Lv, Wanping; Zhuang, Runjie; Wang, Shiyu; Fan, Shuqi; Wen, Yongxian (Frontiers in Plant Science, 2025)
IntroductionPurple eggplant (Solanum melongena L.) is valued for its high anthocyanin content, yet the regulatory mechanisms driving anthocyanin biosynthesis during fruit development remain poorly understood. This study aimed to elucidate the dynamics of anthocyanin accumulation and identify key regulatory genes across three developmental stages of eggplant fruit peel (S1: white, S2: light purple, S3: dark purple).MethodsIntegrated metabolomic and transcriptomic analyses were conducted to investigate anthocyanin profiles and gene expression patterns during fruit development. Metabolomic profiling identified anthocyanin types, while transcriptomic data highlighted differentially expressed genes. Transient overexpression assays of candidate MYB transcription factors (TFs) were performed to validate their regulatory roles in anthocyanin biosynthesis.ResultsTotal anthocyanin content significantly increased as the fruit peel color deepened from S1 to S3. Metabolomic analysis detected 11 distinct anthocyanins, with concentrations rising progressively across stages. Transcriptomics revealed 8 structural genes and 11 MYB TFs enriched in the anthocyanin pathway. Transient overexpression of SmMYB32 and SmMYB67 upregulated key biosynthetic genes (e.g., CHS, DFR, ANS), confirming their role in enhancing anthocyanin production.DiscussionThis study demonstrates that anthocyanin accumulation in eggplant fruit peels is tightly linked to the upregulation of biosynthetic genes and MYB TFs during development. The functional validation of SmMYB32 and SmMYB67 highlights their potential as targets for breeding high-anthocyanin cultivars. These findings advance our understanding of anthocyanin regulation in eggplant and provide actionable strategies for improving nutritional quality through molecular breeding.